Long-Term Effect of Non-Selective Beta-Blockers in Patients With Rheumatoid Arthritis After Myocardial Infarction—A Nationwide Cohort Study - Liu, Sheng-Fu; Lee, Chih-Kuo; Huang, Kuan-Chih; Lin, Lian-Yu; Hsieh, Mu-Yang; Lin, Ting-Tse (Frontiers in Pharmacology, 2021)
Objectives: Rheumatoid arthritis (RA) is an independent nontraditional risk factor for incidence of myocardial infarction (MI) and the post-MI outcome is impaired in RA population. Use of beta-blockers improves the long-term survival after MI in general population while the protective effect of beta-blockers in RA patients is not clear. We investigate the impact of beta-blockers on long-term outcome of MI among RA patients. Methods: We identified RA subjects from the Registry for Catastrophic Illness and myocardial infarction from 2003 to 2013. The enrolled subjects were divided into three groups according to the prescription of beta-blockers (non-user, non-selective and β1-selective beta-blockers). The primary endpoint was all-cause mortality. We adjusted clinical variables and utilized propensity scores to balance confounding bias. Cox proportional hazards regression models to estimate the incidence of mortality in different groups. Results: 1,292 RA patients with myocardial infarction were enrolled, where 424 (32.8%), 281 (21.7%) and 587 (45.5%) subjects were non-user, non-selective and β1-selective beta-blockers, respectively. Use of beta-blockers was associated with lower risk of all-cause mortality after adjustment with comorbidities, and medications (adjusted hazard ratio [HR] 0.871; 95% confidence interval [CI] 0.727 – 0.978) and propensity score (HR 0.882; 95% CI 0.724 – 0.982).Compared with β1-selective beta-blockers, subjects receiving non-selective beta-blockers (HR 0.856; 95% CI 0.702 – 0.984) were significantly related to lower risk of mortality. The protective effect of non-selective beta-blockers remained in different subgroups including sex and different anti-inflammatory drugs. Conclusions: Use of beta-blockers improved prognosis in post-MI patients with RA. Treatment with non-selective beta-blockers were significantly associated with reduced risk of mortality in RA patients after MI rather than β1-selective beta-blockers.